A cycle‐jumping method for multicyclic Hubbert modeling of resource production. (25th November 2020) - Tunnell, Bolorchimeg N.; Conder, James A.; Anderson, Ken B.; Locmelis, Marek
Abstract: The amount of ultimately recoverable resources and/or timing of peak production have been the central purpose of numerous studies. One broadly applied method is Hubbert modeling, subsequently extended as multicyclic Hubbert modeling. This paper explores a modification to conventional multicyclic Hubbert modeling that we term "cycle‐jumping" wherein the overlap of multiple curves is limited and explicitly accounted for. The model is designed in a way that each curve is described by the same three parameters as a multicyclic Hubbert model, and every two curves are connected through an explicit transition. The transition width indicates the time of the shift from one curve to the next and is controlled by a weighting parameter for the respective curves. Cycle‐jumping provides a superior data fit compared to the conventional cycle‐addition model and, more important, reflects historical production data more realistically as socioeconomic and political factors important to resource production vary in time. Recommendations for Resource Managers Conventional multicyclic Hubbert modeling poorly reflects transitions in production trends. Cycle‐jumping with a finite transition period practically and mathematically provides a superior model for historical resource production by limiting the overlap of multiple curves. Cycle‐jumping with a finite transition period reflects more realistically the production profile affected by external factors including capturing inherent asymmetry in different cycles.